Interferometric Scattering Microscopy: Seeing Single Nanoparticles and Molecules via Rayleigh Scattering - Taylor, Richard W.; Sandoghdar, Vahid (Nano Letters, 2019)
Fluorescence microscopy has been the workhorse for investigating optical phenomena at the nanometer scale but this approach confronts several fundamental limits. As a result, there have been a growing number of activities toward the development of fluorescent-free imaging methods. In this Mini Review, we demonstrate that elastic scattering, the most ubiquitous and oldest optical contrast mechanism, offers excellent opportunities for sensitive detection and imaging of nanoparticles and molecules at very high spatiotemporal resolution. We present interferometric scattering (iSCAT) microscopy as the method of choice, explain its theoretical foundation, discuss its experimental nuances, elaborate on its deep connection to bright-field imaging and other established microscopies, and discuss its promise as well as challenges. A showcase of numerous applications and avenues made possible by iSCAT demonstrates its rapidly growing impact on various disciplines concerned with nanoscopic phenomena.
CRIS-Team Scopus Importer:2023-03-27
Keywords: extinction; interferometric microscopy; iSCAT; protein sensing; Rayleigh scattering